Green cardamom plus low-calorie diet can decrease the expression of inflammatory genes among obese women with polycystic ovary syndrome: a double-blind randomized clinical trial - Cheshmeh, Sahar; Ghayyem, Maysa; Khamooshi, Firoozeh; Heidarzadeh-Esfahani, Neda; Rahmani, Negin; Hojati, Niloofar; Mosaieby, Elaheh; Moradi, Shima; Pasdar, Yahya (Eating and weight disorders, 2022)
Purpose Polycystic ovary syndrome (PCOS) is an endocrine disorder and a common cause of infertility among women that is associated with low-grade inflammation. Therefore, the current randomized, double-blind, placebo-controlled clinical trial was conducted to assess the effects of green cardamom supplementation on the serum level of inflammatory markers and their gene expression among obese women with PCOS. Methods We included 194 obese women with PCOS and administered low-calorie diet to all of them. These subjects were randomly divided into two groups including the intervention group with 3 g/day green cardamom ( n = 99) and the placebo group ( n = 95). Anthropometric indices, androgen hormones, and inflammatory factors [tumor necrosis factor-α (TNF-α), interleukin 6 (IL-6), and C-reactive protein (CRP)] were assessed before and after the 4-month intervention. TNF-α, IL-6, and CRP gene expression levels were measured using reverse transcription-polymerase chain reaction (RT-PCR) method. Results Anthropometric indices were improved in both studied groups ( P < 0.001). Among androgen hormones, luteinizing hormone, androstenedione, and dehydroepiandrosterone were significantly decreased ( P < 0.001), and follicle-stimulating hormone was significantly increased ( P < 0.001) in the green cardamom group. Our findings showed that TNF-α, IL-6, and CRP serum levels were significantly decreased after the intervention with green cardamom plus low-calorie diet ( P < 0.001). In addition, the expression levels of TNF-α and CRP genes were significantly decreased in the intervention group ( P < 0.001). Conclusions The present study supports the beneficial anti-inflammatory effect of green cardamom on the inflammatory state in PCOS women. Level of evidence Level I: randomized clinical trial. Trial registration This trial was registered with the Iranian Clinical Trials Registry (registration number: IRCT20200608047697N1). 1 August, 2020; https://www.irct.ir/trial/48748 .